2007
DOI: 10.1073/pnas.0708469104
|View full text |Cite
|
Sign up to set email alerts
|

Conventional dendritic cells regulate the outcome of colonic inflammation independently of T cells

Abstract: We explored the physiological role of conventional dendritic cells (cDCs) in acute colitis induced by a single cycle of dextran sodium sulfate administration. Depending on their mode of activation and independently of T cells, cDCs can enhance or attenuate the severity of dextran sodium sulfate-induced colitis. The latter beneficial effect was achieved, in part, by IFN-1 induced by Toll-like receptor 9-activated cDCs. IFN-1 inhibits colonic inflammation by regulating neutrophil and monocyte trafficking to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 33 publications
9
97
0
Order By: Relevance
“…Similar to the published report, 26 cDC-ablated mice showed less symptom of acute colitis induced by a single cycle of DSS administration than WT mice, whereas there was no significant difference in the attenuation of the development of acute colitis between cDC-ablated and pDC-ablated mice (Supplementary Figure S1f,g). …”
Section: Results Pdc Exacerbates Acute Colitis Induced By a Single-cysupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to the published report, 26 cDC-ablated mice showed less symptom of acute colitis induced by a single cycle of DSS administration than WT mice, whereas there was no significant difference in the attenuation of the development of acute colitis between cDC-ablated and pDC-ablated mice (Supplementary Figure S1f,g). …”
Section: Results Pdc Exacerbates Acute Colitis Induced By a Single-cysupporting
confidence: 89%
“…[26][27][28] Notably, the deficiency of pDCs abrogates colonic inflammation and pathological symptom of acute colitis as well as infiltration of inflammatory leukocytes into inflamed colon in DSS-fed mice. We have previously shown that pDCs could be the primary inflammatory cells to produce cytokines upon recognition of appropriate endosomal TLR ligands and viral components for the induction of systemic inflammation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations